TINJAUAN YURIDIS TERHADAP PERJANJIAN KEMITRAAN DALAM KITAB UNDANG-UNDANG HUKUM PERDATA - Ryan Hidayat (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT“Juridical Review of the Partnership Agreement in Us Civil Law”. Advisor I, Dr. Irman Syahriar S.H., M.Hum and Advisor II Ms. Khairunisah S.H., M. H.Partnership agreements are agreements that are not listed in the Civil Code, but partnership agreements through the principle of freedom of contract in business activities because partnership agreements are often used in business activities, but sometimes the contents of partnership agreements are not in accordance with the principles in an agreement.The purpose of this study is to be able to know the legal review of the partnership agreement in the Civil Code and find out how the Judge's Analysis of the partnership agreement in court decisions.In this paper the author uses this type of research with a normative juridical approach method in which legal research is carried out by examining the literature or secondary data as a basis for research by searching for regulations and literature relating to the problem under study.The results of this study indicate that there were mistakes made by PT. TAKADELI INDONESIA to provide new partnership agreements to second parties or partners who work with PT. TAKADELI INDONESIA and in the contents of the new agreement there is content that makes Partner II feel disadvantaged and also the relationship between partner II and PT. TAKADELI INDONESIA is heating up so PT, TAKADELI is opening a bakery in Ambon where partner II is also opening outlets. The material experienced by Mitra II, in the decision of the Ambon District Court, stated that PT. TAKADELI INDONESIA is guilty and defeated and must pay moral and material losses suffered by Partner II in accordance with the contents of the decision. Keywords: Agreement, Partnership Agreement, Court decision